2016
DOI: 10.3390/ijerph13111105
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluations of the Health Impacts of Weather-Related Extreme Events: A Scoping Review

Abstract: The frequency and severity of extreme events is expected to increase under climate change. There is a need to understand the economic consequences of human exposure to these extreme events, to underpin decisions on risk reduction. We undertook a scoping review of economic evaluations of the adverse health effects from exposure to weather-related extreme events. We searched PubMed, Embase and Web of Science databases with no restrictions to the type of evaluations. Twenty studies were included, most of which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 51 publications
(114 reference statements)
0
22
0
Order By: Relevance
“…The mean annual HN, the mean annual HWD, and HWs affect the human health and the human mortality and can thus be assigned to the health sector (Liu et al, 2017;Patz et al, 2005;Phalkey & Louis, 2016;Schmitt et al, 2016). For the 1.5 and 2°C global warming scenario the model ensemble projects a moderate to strong increase in mean annual HN and for the 3°C global warming scenario a very strong increase in mean annual HN for central Africa (15°S-15°N).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The mean annual HN, the mean annual HWD, and HWs affect the human health and the human mortality and can thus be assigned to the health sector (Liu et al, 2017;Patz et al, 2005;Phalkey & Louis, 2016;Schmitt et al, 2016). For the 1.5 and 2°C global warming scenario the model ensemble projects a moderate to strong increase in mean annual HN and for the 3°C global warming scenario a very strong increase in mean annual HN for central Africa (15°S-15°N).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…There are significant evidence gaps around the economics of health emergency and disaster risk management. Of the economic studies available before the onset of the COVID‐19 pandemic, many did not incorporate economic evaluations, use a societal perspective, or focused on settings in low‐ and middle‐income countries 3‐5 . In the few cases where research projects have been set up to rapidly respond to the emergence of health emergencies, economic studies have been conspicuously absent 37 …”
Section: What Economic Studies Can Domentioning
confidence: 99%
“…Many studies are focusing on the economic impacts associated with the COVID‐19 pandemic, and the costs and consequences of responses targeted to minimize them 2 . Prior to the COVID‐19 pandemic, the economics of sudden‐onset health emergencies and disasters was a rather under‐investigated research area 3‐5 . This is no longer the case 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Floods and droughts, together with other natural disasters, were found to have a particularly damaging impact on the African continent, in particular with respect to fatalities, affected population, and economic damages (Cavallo, 2011). A recent study (Shiferaw et al, 2014), for instance, found that frequent drought conditions have limited the economic growth of many African countries and frustrated the benefits derived from development strategies implemented in the education and technological innovation sectors, confirming the findings of a previous study (Toya and Skidmore, 2007). Reduced precipitation was found to be responsible for about 15 to 40 % of the gap between the per capita gross domestic product of African economies and that of the rest of the developing world (Barrios et al, 2010).…”
Section: Introductionmentioning
confidence: 99%